Experimental Drainage Device to Reduce Lymphoedema in a Rat Model. (June 2019) - Triacca, Valentina; Pisano, Marco; Lessert, Claudia; Petit, Benoit; Bouzourene, Karima; Nahimana, Aimable; Vozenin, Marie-Catherine; Stergiopulos, Nikolaos; Swartz, Melody A.; Mazzolai, Lucia
Abstract : Objective: Despite recent advances in pharmacological research and microsurgery, lymphoedema remains an incurable disease that deeply affects quality of life. There is an urgent need for innovative approaches to restore continuous lymph flow in affected tissues. To this end, the efficacy of a subcutaneously implanted draining device in reducing lymphoedema volume in a rat hindlimb lymphoedema model was tested. Methods: A rat model of chronic lymphoedema was developed by surgical removal of popliteal and inguinal lymph nodes, followed by irradiation. The model was characterised by monitoring limb volume via tape measure, skin water content via dielectric constant measurement, and lymphatic drainage via lymphofluoroscopy. After lymphoedema establishment in 16 Wistar rats, a device made of fenestrated tubing equipped with a miniaturised pumping system, was implanted subcutaneously in the affected limb to restore continuous recirculation of interstitial fluid. Results: Lymphofluoroscopy imaging showed impaired lymphatic drainage following lymphadenectomy and irradiation. Affected limb volume and skin water content increased significantly compared with the untreated limb, with a median (interquartile range) of 3.85 (0.38) cm 3 versus 3.03 (0.43) cm 3 for volume ( n  = 16, p  = .001) and 26.6 (9.1) versus 16.6 (3.7) cm 3 for skin dielectric constant ( n  = 16, p  = .001). Treatment of lymphoedema with the implanted drainage device showed that 5 weeks post-implant excess volume was significantly reduced by 51 ± 18% compared with the pre-implant situation ( n  = 9 sham group, n  = 7 pump group). Conclusion: Lymphoedema volume in the rat model was significantly reduced by restoring continuous drainage of excess fluid using a novel subcutaneously implanted device, opening the way to the development of an artificial lymphatic vessel.